Early pregnancy termination with a simplified mifepristone: Medical abortion outpatient regimen - Chuni, N; Chandrashekhar, TS (Kathmandu University Medical Journal, 2010)
Background: An estimated 30 million abortions are performed worldwide every year. Many women do not have access to abortion and die of complications after illegal abortions. Medical abortion could provide greater access to safe abortion services; availability of the procedure is, therefore, of global public health importance. Aim: The aim was to study the efficacy of lowered dose of Mifepristone in medical abortion. Materials and methods: One hundred and twelve cases with a pregnancy of 63 days duration or less were enrolled in a prospective study using a lowered dose of 200mg Mifepristone followed, 48 hours later, by home administration of 400μg Misoprostol orally. At the second visit, on day 15, outcome and adverse effects were analysed. Women who failed to undergo a complete abortion were further managed by surgical evacuation of uterus. Results: The mean gestational age was 50.6 days. The rates of complete abortion were 92.8%, 83 % and 80 % in the ≤49 days group, 50 to 56 days and 57 to 63 days group respectively. Vaginal bleeding emerged as the biggest reason for medically indicated termination. Nulliparous women had a greater frequency of side effects, though values did not reach statistical signifi cance. Conclusion: This regimen of a lower dose of 200mg Mifepristone, followed by home administration of 400μg oral Misoprostol 48 hours later is safe and highly effective especially in pregnancies of up to 49 days duration. Key words: Mifepristone; Medical termination of pregnancy (MTP) DOI: 10.3126/kumj.v7i3.2725 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 209-212